2012
DOI: 10.4081/idr.2012.e25
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and its effects on the visual system

Abstract: During the first 15 years of the AIDS epidemic patients experienced a high incidence of blindness due to cytomegalovirus (CMV) retinitis and other severe ocular opportunistic infections. Highly active anti-retroviral therapy, introduced in 1996, dramatically decreased the incidence of CMV retinitis. Though CMV retinitis still causes 40% of vision loss in AIDS patients, other conditions such as immune reconstitution uveitis, cataracts, and a significant othercategory -which most investigators believe is directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that HIV could be recovered from multiple ocular tissues, such as the retina, conjunctiva, cornea, and iris of patients with AIDS [23, 24]. We documented the presence of intraocular HIV RNA in 32% of consecutive HIV-infected patients with intraocular inflammation.…”
Section: Introductionmentioning
confidence: 71%
“…Previous studies have shown that HIV could be recovered from multiple ocular tissues, such as the retina, conjunctiva, cornea, and iris of patients with AIDS [23, 24]. We documented the presence of intraocular HIV RNA in 32% of consecutive HIV-infected patients with intraocular inflammation.…”
Section: Introductionmentioning
confidence: 71%
“…On the other hand, to our knowledge, this is the first study to report a significant association between old age and HIV retinopathy. HIV retinopathy is a well-known ocular disease characterized by micro aneurysms, telangiectasia, retinal hemorrhages, and CWS [ 7 ]. Pathogenesis and clinical significance of HIV retinopathy are not fully understood, and number of probable etiologies or associated factors, including viral immune complex, direct HIV infection of endothelial cells, and hyperviscosity due to red cell aggregation, have been suggested [ 7 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMV retinitis which fulfilled the standard ACTG criteria of “confirmed CMV retinitis” was included as CMV retinitis cases which required a diagnosis by an experienced ophthalmologist and documentation of CMV retinitis by retinal photography [ 13 ]. The diagnosis of HIV retinopathy was based on the findings of microaneurysms, telangiectasia, retinal hemorrhages, and cotton wool spots (CWS) [ 7 ]. The diagnosis of ocular syphilis was based on 1) ophthalmological examination documenting findings specific to ocular syphilis and 2) evidence of syphilis infection defined by a positive serum quantitative rapid plasma reagin (RPR) (titer ≥8) and positive Treponema pallidum hemagglutination assay [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-related MVR refers to non-infectious retinal vascular changes. The diagnosis was based on the findings of microaneurysms, telangiectasia, retinal hemorrhages, and cotton wool spots (CWS) [11] . One assumption regarding the pathogenesis of HIV/AIDS-related retinopathy is that HIV-1 can induce an inflammatory state in human retinal pigment epithelial (HRPE) cells, which results in impairment of HRPE barrier function [12] .…”
Section: Discussionmentioning
confidence: 99%